The Medieval Culture of Disputation : Pedagogy, Practice, and Performance - Novikoff, Alex J. (Book collections on Project MUSE., 2013)
Through hundreds of published and unpublished sources, Alex J. Novikoff traces the evolution of disputation from its ancient origins to its broader influence in the scholastic culture and public sphere of the High Middle Ages.